A Study on Gender Non-Conforming Subjects in Current Society: Self-Perception of Body and Identity - Martínez, Ariel (2015)
This article presents the results of a research to be included in a PhD Thesis on Gender non-conformity. Behind the results there is bibliographic research and fieldwork with 11 subjects over 18 years-old from La Plata and La Plata metropolitan area. The theoretical framework doesn?t look into the specific realities of gender non-conforming subjects. I attempted to explore the subjects? narrations on themselves and their self-perception with a quantitative view. From a diversity standing point, all narrations shed light on key aspects about social and subjective construction of gender and its naturalization as gender conformity. In addition, the results of empirical research are shortly laid out. Research had a focus on the ways gender non-conforming subjects name themselves, how they recreate categories from a singular point of view and the place of the body in self-perceptions about gender identity